Selectivity-based management for reversing overexploitation of demersal fisheries in North-western Mediterranean Sea - N. Bahamon; L. Recasens; J. Sala-Coromina; B. Calero; J.A. Garcia; G. Rotllant; A. Maurer; A. Rojas; L. Muth; J. Quevedo; M. Vigo; J. Ribera-Altimir; et al. (Marine Policy, 2024)

High environmental salinity reduces the reproductive potential of the spider crab M aja brachydactyla ( D ecapoda, M ajidae) - Guiomar Rotllant; Carles G. Simeó; Glòria Macià; Alicia Estévez (Marine Ecology, 2015)
The spider crab M aja brachydactyla is an important fisheries species in E urope. Adults were sampled in R ía de A C oruña ( NW S pain) and transported to IRTA rearing facilities. Salinity and photoperiod changes and their effect on reproduction were tested in the laboratory. The number of newly hatched larvae per batch (presence of actively swimming newly hatched larvae in a broodstock tank) was counted and sampled to estimate dry weight and proximal composition. Keeping spider crab broodstock in a high salinity environment (38 ppt) significantly reduced the number of newly hatched larvae, reaching up to fivefold difference in winter. The number of newly hatched larvae produced under a natural photoperiod was 10‐fold higher than those produced using a fixed photoperiod at 34 ppt salinity during winter. No clear pattern of changes in larval dry weight, protein, lipid or carbohydrate composition was observed under the environmental conditions tested. The results show that the salinity used for broodstock maintenance, especially during the embryonic development, is an important factor causing changes in larval production of M . brachydactyla and with potential implications for recruitment success.

Pilot acoustic tracking study on adult spiny lobsters (Palinurus mauritanicus) and spider crabs (Maja squinado) within an artificial reef - Guiomar Rotllant; Jacopo Aguzzi; David Sarria; Enric Gisbert; Valerio Sbragaglia; Joaquín Del Río; Carles G. Simeó; Antoni Mànuel; Erik Molino; Corrado Costa; Francisco Sardà (Hydrobiologia, 2015)

Interannual variability in the biochemical composition of newly hatched larvae of the spider crab Maja brachydactyla (Decapoda, Majidae) - Guiomar Rotllant; Carles G. Simeó; Guillermo Guerao; Marta Sastre; Daniel F. R. Cleary; Ricardo Calado; Alicia Estévez (Marine Ecology, 2014)
The spider crab M aja brachydactyla is an important commercial species in E urope and supports intensive fisheries in the NE Atlantic. A field survey was performed to assess long‐term and consecutive interannual (2005–2010) variation of the biochemical composition of newly hatched larvae of M . brachydactyla . L arval biochemical profiles differed significantly among years, with pronounced differences being recorded in 2010. Differences among batches of newly hatched larvae were mainly explained by the contribution of triacylglycerols and, to a lesser degree, by protein and lipid content. The use of different nutrition indices is discussed. The biochemical composition of newly hatched larvae from M . brachydactyla was highly variable, even though surveyed broodstock was obtained from the same local population and was always sampled during the same season. The unpredictable biochemical profiles of newly hatched larvae may condition their survival and recruitment. This largely overlooked aspect of larval variability should be considered in future fisheries management strategies and captive production of marine organisms that still rely on wild seeds.

Population structure and reproductive patterns of the NW Mediterranean deep-sea macrourid Trachyrincus scabrus (Rafinesque, 1810) - U. Fernandez-Arcaya; L. Recasens; H. Murua; E. Ramirez-Llodra; G. Rotllant; J. B. Company (Marine Biology, 2012)

Biological patterns and ecological indicators for Mediterranean fish and crustaceans below 1,000 m: a review - F. Sardà; J. B. Company; G. Rotllant; M. Coll (Reviews in Fish Biology and Fisheries, 2009)

Environmental influences on zooplankton and micronekton distribution in the Bransfield Strait and adjacent waters - I. A. Catalán; B. Morales-Nin; J. B. Company; G. Rotllant; I. Palomera; M. Emelianov (Polar Biology, 2008)

Synchronous moulting of krill, Euphausia superba , in the Bransfield Strait (Antarctica) - G. Rotllant; J. B. Company; X. Busquets; F. Buchholz (Polar Biology, 2004)

Inhibition of HPI axis response to stress in gilthead sea bream (Sparus aurata) with physiological plasma levels of cortisol - J. Rotllant; R.J. Arends; J.M. Mancera; G. Flik; S.E. Wendelaar Bonga; L. Tort (Fish Physiology and Biochemistry, 2000)